Dual Roles of Glutathione in Ecdysone Biosynthesis and Antioxidant Function During Larval Development in Drosophila. Issue 4 (11th October 2017) - Enya, Sora; Yamamoto, Chikana; Mizuno, Hajime; Esaki, Tsuyoshi; Lin, Hsin-Kuang; Iga, Masatoshi; Morohashi, Kana; Hirano, Yota; Kataoka, Hiroshi; Masujima, Tsutomu; Shimada-Niwa, Yuko; Niwa, Ryusuke
Abstract: Ecdysteroids, including the biologically active hormone 20-hydroxyecdysone (20E), play essential roles in controlling many developmental and physiological events in insects. Ecdysteroid biosynthesis is achieved by a series of specialized enzymes encoded by the Halloween genes. Recently, a new class of Halloween gene, noppera-bo ( nobo ), encoding a glutathione S -transferase (GST) in dipteran and lepidopteran species, has been identified and characterized. GSTs are well known to conjugate substrates with the reduced form of glutathione (GSH), a bioactive tripeptide composed of glutamate, cysteine, and glycine. We hypothesized that GSH itself is required for ecdysteroid biosynthesis. However, the role of GSH in steroid hormone biosynthesis has not been examined in any organisms. Here, we report phenotypic analysis of a complete loss-of-function mutant in the γ -glutamylcysteine synthetase catalytic subunit ( Gclc ) gene in the fruit fly Drosophila melanogaster . Gclc encodes the evolutionarily conserved catalytic component of the enzyme that conjugates glutamate and cysteine in the GSH biosynthesis pathway. Complete Gclc loss-of-function leads to drastic GSH deficiency in the larval body fluid. Gclc mutant animals show a larval-arrest phenotype. Ecdysteroid titer in Gclc mutant larvae decreases, and the larval-arrest phenotype is rescued by oral administration of 20E or cholesterol. Moreover, Gclc mutant animals exhibit abnormal lipid deposition in the prothoracic gland, a steroidogenic organ during larval development. All of these phenotypes are reminiscent to nobo loss-of-function animals. On the other hand, Gclc mutant larvae also exhibit a significant reduction in antioxidant capacity. Consistent with this phenotype, Gclc mutant larvae are more sensitive to oxidative stress response as compared to wild-type. Nevertheless, the ecdysteroid biosynthesis defect in Gclc mutant animals is not associated with loss of antioxidant function. Our data raise the unexpected hypothesis that a primary role of GSH in early D. melanogaster larval development is ecdysteroid biosynthesis, independent from the antioxidant role of GSH.